Faktor-faktor yang mempengaruhi financial distress bank syariah yang terdaftar di OJK tahun 2016-2020 - Anis Fathul Rizqi; Sunarsih Sunarsih (LPMP Imperium, 2022)
The components of Risk Based Bank Rating, Bank Size, Inflation, and Interest Rates on Financial Distress of Islamic commercial banks registered with the Financial Services Authority in 2016-2020 are analyzed in this study. Using panel data regression analysis, the test results prove that the ROA, CAR, and GCG variables significantly negatively affect financial distress. The variable bank size has a significant positive effect on financial distress. While the NPF, FDR, Inflation, and BI rate variables do not affect financial distress.